1981
DOI: 10.1139/m81-065
|View full text |Cite
|
Sign up to set email alerts
|

Polygalacturonic acid transeliminase production by Azospirillum species

Abstract: Polygalacturonic acid transeliminase (PATE) was produced by all of six Azospirillum strains studied. Characteristics were similar to those of PATE from other bacteria: activity was maximal at pH 8.0 and was stimulated by CaCl2. Polygalacturonic acid was used more readily than pectin as a substrate. Polygalacturonic acid in the medium stimulated PATE production by several but not all strains. In all cases some of the PATE produced in cultures remained bound to cell walls. In one strain, most remained cell wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…A species of rhizotrophic bacteria, Azospirillum sp., can produce the growth promoting factor auxin such as indol-3-acetic acid. 21) We also investigated high auxin producing bacteria. As shown in Fig.…”
mentioning
confidence: 99%
“…A species of rhizotrophic bacteria, Azospirillum sp., can produce the growth promoting factor auxin such as indol-3-acetic acid. 21) We also investigated high auxin producing bacteria. As shown in Fig.…”
mentioning
confidence: 99%
“…In the legume-Rhizobium symbiosis, ultrastructural studies provided evidence that rhizobial cellulases may be involved in various steps of the infection process (8,9). The grass-associated diazotroph Azospirillulm brasilense, although able to colonize the interior of grass roots (35,51), is pectinolytic (55), but so far no cellulolytic activity has been reported to be present. Cellulose only supported growth of Azospirillum cells in coculture with cellulolytic bacteria (22).…”
mentioning
confidence: 99%
“…There is no obvious evidence for producing cellulase by Azospirillum and the reports of pectinolytic activity of Azospirillum brasilense are contradictory. Several authors (Plazinski and Rolfe 1985;Tien et al 1981) have reported pectinolytic activity but others (Khammas and Kaiser 1991;Myers and Hubbell 1987) have found no evidence of pectin breakdown by A. irakens. However, it is also possible that Azospirillum does not produce the complete enzyme set required for the infection but induces plant to produce these enzymes by e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Polygalacturonic acid and pectin are utilized by Azospirillum brasilense Sp7 in broth culture and on agar plates (Umali-Garcia et al 1980). Polygalactacturonic acid transeliminase (pectic lyase) activity has been detected in strain Sp7 culture (Tien et al 1981). It has been suggested that the ability of Azospirillum spp to degrade pectin could assist in the penetration of the middle lamellae of grass roots (Umali-Garcia et al 1980).…”
Section: Introductionmentioning
confidence: 99%